An examination of the right to health of people living with HIV/AIDS in Nigeria (2017)
Human Immunodeficiency Virus (HIV) and Acquired Immune Deficiency Syndrome (AIDS) is a serious public health challenge in Nigeria, and the world at large. Anyone and everyone can become its victim as it can be contacted sexually or otherwise such as through blood transfusion, blade, pin or needle. However, some groups of people are more vulnerable to contact the disease than others, and unfortunately, the former’s human rights, particularly, their rights to health have been denied by their loved ones, communities and the government, thus, exposing them to various forms of discrimination and social exclusion. Thus, this article shall discuss the concepts of human rights, right to health, and HIV/AIDS. It will also discuss the complicated relationship between HIV/AIDS and human rights, specifically right to health; and also examine the legal framework on the right to health in Nigeria provided for by international and regional treaties of which Nigeria is signatory, and her local laws. Furthermore, it will consider the vulnerable groups of people living with HIV/AIDS (PLWHA) in Nigeria. Additionally, it will examine the extent to which rights to health are enjoyed by PLWHA in Nigeria. Finally, it will conclude by recommending solutions to the denial of treatment in Nigerian health care institutions.